Clinical frailty scale as a predictor of disease severity in patients hospitalised with COVID-19 – an observational cohort study. Issue 8 (3rd August 2022) - Mattsson, Gustav; Gonzalez Lindh, Margareta; Razmi, Robin; Forslin, Mia; Parenmark, Fredric; Bandert, Anna; Ehrenborg, Christian; Palm, Andreas
Abstract: Background: The coronavirus disease 2019 pandemic makes proper resource allocation and prioritisation important. Frailty increases the risk of adverse outcomes and can be quantified using the Clinical frailty scale. The aim of this study was to determine the role of the Clinical frailty scale, in patients ≥65 years of age with coronavirus disease 2019, as a risk factor either for critical coronavirus disease 2019 measured as intensive care unit admission or death or as a risk factor for death. Methods: This was a retrospective observational study on patients ≥65 years hospitalised with coronavirus disease 2019 verified by polymerase chain reaction between 5 March 5 and 5 July 2020. The association between Clinical frailty scale and the composite primary outcome intensive care unit admission or death within 30 days post hospitalisation and the secondary outcome death within 30 days post hospitalisation was analysed using multivariable logistic regression models adjusting for gender, age, body mass index, hypertension, and diabetes. Clinical frailty scale was used as a categorical variable (fit score 1–4, frail score 5–6, and severely frail score 7–9). Results: In total, 169 patients were included (47.3% women, mean age 79.2 ± 7.8 years). In the fully adjusted model, adjusted odds ratio for intensive care unit admission or death was 1.84 (95%-confidence interval 0.67–5.03, p  = .234) for frail and 6.08 (1.70–21.81, p  = .006) for severely frail compared to fit patients. For death, adjusted odds ratio was 2.81 (0.89–8.88, p  = .079) for frail and 9.82 (2.53–38.10, p  = .001) for severely frail compared to fit patients. Conclusions: A high Clinical frailty scale score was an independent risk factor for the composite outcome intensive care unit admission or death and for the secondary outcome death.